Do consumers' purchase intentions differ for prototypical and me-too brands in the banking industry - Quintal, Vanessa; Phau, Ian (Adilson Borges, Reims Management School, France, 2011)
This paper aims to examine the antecedents of purchase intention for their differential impacts between prototypical and metoo brands in the banking industry. To achieve this, a pen and paper survey was administered to a random sample of the population in Western Australia. For the prototypical brands, extrinsic attributes and perceived risk played influential roles, with extrinsic attributes directly and positively and perceived risk directly and negatively impacting on purchase intention. This raises some concern for the prototypical brand as it suggests that it is highly dependent on its extrinsic attributes to appeal to consumers. For the me-too brands, perceived quality positively mediated the brand familiarity-purchase intention relationship. This is encouraging for the me-too brands as it suggests that in a marketplace where banks are viewed with suspicion, smaller, community me-too brands that are familiar to consumers, enjoy a reputation for service quality that impacts positively on purchase intention.